The Role of Microbial Inoculants on Plant Protection, Growth Stimulation, and Crop Productivity of the Olive Tree (Olea europea L.) - Georgios Bizos; Efimia M. Papatheodorou; Theocharis Chatzistathis; Nikoletta Ntalli; Vassilis G. Aschonitis; Nikolaos Monokrousos (Plants, 2020)
The olive tree (Olea europaea L.) is an emblematic, long-living fruit tree species of profound economic and environmental importance. This study is a literature review of articles published during the last 10 years about the role of beneficial microbes [Arbuscular Mycorrhizal Fungi (AMF), Plant Growth Promoting Rhizobacteria (PGPR), Plant Growth Promoting Fungi (PGPF), and Endophytes] on olive tree plant growth and productivity, pathogen control, and alleviation from abiotic stress. The majority of the studies examined the AMF effect using mostly Rhizophagus irregularis and Glomus mosseae species. These AMF species stimulate the root growth improving the resistance of olive plants to environmental and transplantation stresses. Among the PGPR, the nitrogen-fixing bacteria Azospirillum sp. and potassium- and phosphorous-solubilizing Bacillus sp. species were studied extensively. These PGPR species were combined with proper cultural practices and improved considerably olive plant’s growth. The endophytic bacterial species Pseudomonas fluorescens and Bacillus sp., as well as the fungal species Trichoderma sp. were identified as the most effective biocontrol agents against olive tree diseases (e.g., Verticillium wilt, root rot, and anthracnose).